The interplay of factors affecting online learning experience in higher education - Fredy, Fredy; Purwanty, Ratna; Sari, Desy Kumala; Prihandoko, Lastika Ary (International Journal of Evaluation and Research in Education (IJERE), 2024)
Education has undergone a profound transformation, transitioning significantly from traditional face-to-face instructional approaches to a predominant reliance on online learning methodologies. This sudden change leaves questions on how to provide an affective and satisfying online leaning for students. As prior studies revealed, many factors affect the success of implementing online learning, specifically for higher education students. As a response, this quantitative study was intended to investigate the interplay of factors affecting online learning experience in higher education namely anxiety, motivation for learning, self-directed learning, online learning attitude, and computer-internet self-efficacy. An exploratory factor analysis (EFA) included 20 items of online survey distributed to undergraduate students (n=329) from several faculties at one Indonesian university to explore this issue. This study used the partial least squares structural equation modeling (PLS-SEM) application to explore the interplay among six constructs. The results showed that all six constructs namely anxiety, motivation for learning, self-directed learning, online learning attitude, computer-internet self-efficacy, and online learning experience were positively associated. It meant that those factors were statistically proven to affect students’ online learning experiences. Educators could use these results as a consideration in implementing online learning more effectively. Further implications of pedagogical practice and further research are discussed.